Pedagogical problems of harmonization of the management system of a preschool educational organization - Umarova Mukaddas Mukhtarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the development of new models that serve to expand the possibilities of scientific and methodological management of preschool education organizations is of particular importance, and this model is based on the development of new parameters for managing the organization of preschool education.